Социология федерализма: историографический аспект анализа - Городяненко, В. (Социология: теория, методы, маркетинг, 2008)
The paper analyzes literary sources covering the problems of state governing. The author devotes his attention to the experience of foreign nations gained under for mation and development of federal governing, as well as emphasizes others’ opinions and suggestions about the state governing of Ukraine.